2012
DOI: 10.1016/j.joca.2012.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The extent of degeneration of cruciate ligament is associated with chondrogenic differentiation in patients with osteoarthritis of the knee

Abstract: This study indicates that chondrogenic differentiation is associated with the progression of degeneration in human ligaments. Our results suggest that the expression of SOX9 as a chondrogenic marker could be an indicator for the extent of degeneration in human ligaments. It remains to be elucidated whether suppression of chondrogenic differentiation can prevent progression of the degenerative process of cruciate ligaments in patients with OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 41 publications
1
37
1
Order By: Relevance
“…Our findings of increased expression of genes of the WNT signaling pathway in the Achilles tendon-to-bone insertion of mstn −/− mice from neonatal to middle age support the hypothesis that myostatin deficiency contributes to ankle dysfunction. For instance, myostatin promotes tenocytes proliferation and differentiation while inhibiting chondrocyte differentiation in cell culture, indicating that myostatin may mitigate calcification and degeneration of juxta-articular ligaments (4042). Myostatin also inhibits expression of BMP2 and IGF1, decreases osteoblast differentiation, and reduces mineral formation in bone marrow-derived mesenchymal stem cells (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of increased expression of genes of the WNT signaling pathway in the Achilles tendon-to-bone insertion of mstn −/− mice from neonatal to middle age support the hypothesis that myostatin deficiency contributes to ankle dysfunction. For instance, myostatin promotes tenocytes proliferation and differentiation while inhibiting chondrocyte differentiation in cell culture, indicating that myostatin may mitigate calcification and degeneration of juxta-articular ligaments (4042). Myostatin also inhibits expression of BMP2 and IGF1, decreases osteoblast differentiation, and reduces mineral formation in bone marrow-derived mesenchymal stem cells (43, 44).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SOX9 staining was increased significantly in the cranial cruciate ligaments of the eTPA stifles compared to the control stifles. SOX9 is expressed in mesenchymal stem cells, pre-chondrocytes, and chondrocytes, and directs mesenchymal stem cells to undergo chondrogenic differentiation and activate transcription of chondrocyte-specific genes such as COLII (20). Bi and colleagues reported that SOX9-/-cells do not express chondrocytespecific markers, including COLII, and suggested SOX9 as the first transcription factor essential for chondrocyte differentiation and cartilage formation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Bone attachment sites were excluded from the analysis. nate cellular long axis were defined as round ligamentocytes, and all other ligamentocytes were considered spindle ligamentocytes (20). The percentage of positive ligamentocytes was calculated as follows: (number of positive ligamentocytes/ total number of ligamentocytes) × 100.…”
Section: Postoperative Tpa and Mmptamentioning
confidence: 99%
“…The relationship between ACL degeneration and OA has been examined in earlier studies (). Typically, degenerative changes in the ACL start with collagen fiber disorientation, followed by mucoid degeneration, inflammatory cell infiltration, and/or neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…It thus appears that ligament/tendon may contain a substantial proportion of progenitor cells. In OA, progenitor cells are activated, abnormally expressing SOX9 and differentiating to chondrocyte‐like cells (). Although these abnormal cells in degenerated ACLs are frequently positive for SOX9, other chondrogenic markers such as type II collagen or aggrecanase are not expressed by all of these cells.…”
Section: Discussionmentioning
confidence: 99%